Memikirkan Ulang Bisnis Model Berbasis Desain Komunikasi Visual - Wiryawan, Mendiola B. (Bina Nusantara University, 2011)
Graphic design as an applied art started to grow side by side with the growth of many businesses that needed promotion and advertising. Although graphic design can be categorized as a service company, it cannot be directly handled the same as any other service companies. Design companies always involve two opposite poles: aesthetic vs. logic, individual vs. mass, idealism versus reality. The best way viewing a graphic design as a business entity is seeing through its business model?s side. A business model is a simple representation of the complex reality of a business. The primary purpose of a business model is to communicate business mechanism among stakeholders. The article gives insight to see components of graphic design business and their future challenge. In the future, it is expected there are more discussions about this topics so that Indonesian graphic design industry will grow in the future.